Figurative Language And Meaning In Bangtan Sonyeondan (BTS)'s And Michael Jackson's Songs - wirdayanthi, gung istri (Udayana Journal of Social Sciences and Humanities; Vol 7 No 2 (2023): Vol 7 No 2 (2023): UJoSSH, September 2023DO - 10.24843/UJoSSH.2023.v07.i02.p03, 2024)
This article entitled “Figurative Language In Bangtan Sonyeondan (BTS)’s And Michael Jackson’s Songs”. This study aims to find out the types of figurative language in the song lyrics. “Dynamite” song was popularized by the South Korean boyband BTS and “Loving You” song was popularized by Michael Jackson. In this study, the data was taken from the song lyrics in each line, then looking for words that belong to the types of figurative language and to analyse using a qualitative method. The theory for the analysis used the figurative language theory by Knickerbocker and Renninger (1974) and is supported by the theory of meaning by Leech (1974). The results of the study shows, the types of figurative language used are hyperbole, personification, allusion, simile, metaphor, synechdoche, metonymy, irony, and symbol.